Establishing a European wastewater pathogen monitoring network employing aviation samples: a proof of concept - Robert Morfino; Bernd Manfred Gawlik; Simona Tavazzi; Angela Tessarolo; Ana Burgos Gutierrez; Nita K. Madhav; Jasmine Grimsley; Amy Schierhorn; Andrew Franklin; Marta Vargha; Andrew Engeli; Mitchell Wolfe (Human Genomics)
Abstract Pathogens know no borders, and the COVID-19 pandemic highlighted the urgent need for comparable, globally accessible pathogen data. This paper proposes a European wastewater pathogen monitoring network using aircraft and airport samples as a proof of concept for an effective cross-national surveillance system. The study emphasizes the importance of genomic data collection from strategic sites to produce high-value data for disease surveillance and epidemiological analysis. The authors suggest establishing "Super Sites" in key locations, particularly major transportation hubs like airports, to serve as focal points for wastewater-based pathogen surveillance. The European Commission has identified over 20 candidate Super Sites and supports their integration into a Global Wastewater Sentinel System. In October 2023, the European Commission’s Joint Research Centre (JRC) and Ginkgo Bioworks conducted an ad hoc exercise, collecting and analyzing wastewater samples from airports and aircraft across Europe. This exercise demonstrated the feasibility of coordinated sampling, centralized processing, and data sharing across different countries. Samples were collected from eight airports over two weeks, employing various methods for different types of wastewater, including samples from terminals and aircraft. Across airports, 96% of wastewater samples tested positive for SARS-CoV-2, with similar viral loads between aircraft and airport sewage, and multiple lineages were identified, including the EG.5 variant, which is consistent with the publicly reported variant data. The results underscore the potential of routine aircraft wastewater monitoring as an early warning system for emerging pathogens. The study also highlights the need for standardized protocols and real-time reporting systems and the importance of addressing ethical considerations in handling passenger data. By creating a network of Super Sites, and integrating cross-national wastewater surveillance data with passenger flight data, the European Union aims to strengthen global public health responses to future pandemics. Establishing this surveillance network is a crucial step towards a pan-European surveillance system for pathogens, providing a non-intrusive complement to existing systems that rely on individual testing. This system will significantly improve early detection capabilities, leading to more rapid and robust responses and ultimately enhancing global health security.